WORK LIFE BALANCE DAN PENGARUHNYA TERHADAP KEPUASAN KERJA KARYAWAN PT. NASMOCO BAHTERA MOTOR JANTI - Natoil, Natoil; Ernawati, Fidyah Yuli; Linanjung, Yolanda Ardestya; Khayatun, Siti (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
Companies must consider the level of satisfaction of each employee because satisfaction is a crucial factor for the company, as job satisfaction is a criterion for determining a company's success in meeting its employees' needs. This study was conducted to determine and analyze the influence of work-life balance, work environment, and leadership on employee job satisfaction at PT. Nasmoco Bahtera Motor Janti. This study used quantitative methods. The research subjects were PT. Nasmoco Bahtera Motor Janti employees. The sample size was 94. Data collection techniques used were questionnaires and literature reviews. The analytical methods used were Descriptive Statistical Analysis, Classical Assumption Testing, Model Feasibility Testing, Multiple Linear Regression, t-tests, and F-tests. . The results of the t test of the work life balance variable do not have a significant effect on employee job satisfaction at PT. Nasmoco Bahtera Motor Janti, seen from the t count on the work life balance variable, the t count value is 1.745. While the t table value (a = 0.05, dk = n-k-1, dk = 94-3-1 = 90) is 1.986. t count (1.745) < t table (1.986) (Ha is rejected and Ho is accepted).The work environment variable has a significant influence on the job satisfaction of employees of PT. Nasmoco Bahtera Motor Janti, seen from the t count on the work environment variable, the t count value is 4.382. While the t table value (a = 0.05, df = n-k-1, df = 94-3-1 = 90) is 1.986. t count (4.382) > t table (1.986) (Ho is rejected and Ha is accepted) and the leadership variable does not have a significant influence on the job satisfaction of employees of PT. Nasmoco Bahtera Motor Janti, seen from the t count on the leadership variable, the t count value is 0.012. While the t table value (a = 0.05, df = n-k-1, df = 94-3-1 = 90) is 1.986. t count (0.012) < t table (1.986) (Ha is rejected and Ho is accepted). Based on this research, the author offers several suggestions for improving employee job satisfaction: developing a work system, organizing work in accordance with standard procedures, and creating a more comfortable work environment so that employees feel more comfortable and safe in the workplace, which will ultimately increase employee job satisfaction